Literature study: The Efficiency of Aquaponic Systems in Fish and Crop Production: A Case Study in an Urban Environment - Bruri M Laimeheriwa; Sophia N. M. Fendjalang (Grouper, 2024)
Aquaponics is a system that integrates fish cultivation with plant cultivation in a mutualistic symbiotic manner. This system uses wastewater from fish as nutrients for plants, while the plants clean the water through root filtration. This paper aims to analyze the efficiency of aquaponic systems in fish and plant production, with a focus on case studies conducted in urban environments. The analysis results show that the aquaponics system in fish and plant production in urban environments can achieve a high level of efficiency. This system is more efficient than conventional cultivation methods bein terms of water use cause water can be reused and not wasted. Efficiency in energy use is also visible because aquaponic systems reduce energy requirements for water circulation and environmental maintenance of plants. In addition, analysis of the nutritional efficiency of the aquaponic system shows that nutrients from fish waste can be utilized optimally by plants so that the use of additional fertilizer can be reduced. This has positive implications in terms of cost savings and reduced environmental impact. This case study shows that aquaponic systems are a potential solution to increase the efficiency of fish and plant production, especially in urban environments where land and resources are limited. Apart from production efficiency, this system also has additional benefits, such as local food production, reduction of organic waste, and development of sustainable agriculture.